Influencia de la inversión pública en la actividad económica del departamento de Loreto, periodo 2018 – 2022 - Cardenas Rengifo, Raisa Juliana (2024)
Economic theory maintains that public investment has to be well directed so that it has a positive impact on the economy, otherwise it slows down product growth and the much-required multiplier is not activated. The objective of this thesis is to determine the influence of public investment on the economic activity of the department of Loreto, during the period 2018 - 2022. This research is Quantitative, Correlational level and Non-Experimental in design. It concludes that public investment does not influence the economic activity of Loreto, during the period 2018 – 2022, validating with the Correlation Coefficient which was r = 0.364510308; and with the Coefficient of Determination it was R2 = 0.132867764; both values that do not reach the required minimums. The level of government that executed the largest amount of public investment was the Regional Government, executing 40.68% of the total equivalent to S/. 2,338,900.00 thousand, dedicated mainly to infrastructure and equipment works, as well as the construction and maintenance of access roads. The Transportation and Communications economic activity concentrates the largest investment amounting to S/. 2,058,800.00 thousand, an amount that represents 35.81% of the total. The development of the regional economy was done through the study of the Gross Added Value (GVA), and the Extraction of Oil, Gas and Minerals made the highest contribution, reaching 18.24% of the total.